Sports Marketing and Perceived Value: an application of the conjoint analysis in the Fan Membership Programs of Football - Pâmela de Souza Dias; Plínio Rafael Reis Monteiro (BBR: Brazilian Business Review)
Football is ever present in Brazilians’ lives, and, more than a game, it also involves social and economic relations. Fan Membership Programs (FMPs), based on relationship marketing strategies, are ways to bring the clubs closer to their fans. This paper aims to analyze the perceived value structure of FMPs, based on sociodemographic profiles, starting with FMP attributes of the 2016 Brazilian Football Championship series A classified clubs. The data was collected online, and the population consisted of fans of the selected teams. The data was analyzed using the multivariate technique of Conjoint Analysis. It was verified that the general sample for different sociodemographic profiles, the ticket discounts, and prices of the FMP are the most valued attributes. This paper contributes to academy and practice by presenting a capable instrument to describe FMPs’ value perception. In academic terms, it contributes as a sports marketing management study. In addition, the paper could also apply as a tool for the Football clubs’ managers.